Histamine intolerance in patients with chronic spontaneous urticaria. (22nd June 2016) - Siebenhaar, F.; Melde, A.; Magerl, M.; Zuberbier, T.; Church, M.K.; Maurer, M.
Abstract: Background: Histamine intolerance and pseudoallergy to foods have been suggested to be causes of chronic spontaneous urticaria (CSU) with some patients reporting exacerbation with histamine‐rich foods. Objective: The study aim was to identify the rate of histamine‐intolerant CSU patients and to characterize the relevance of histamine intolerance as an underlying cause of CSU. Methods: A cohort of 157 of moderate to severe CSU patients (UAS7 ≥ 10) was asked to provide a detailed clinical history, particularly in relation to symptom development after eating histamine‐rich foods. They subsequently undertook a histamine‐free pseudoallergen‐low diet followed by a double‐blind, placebo‐controlled oral histamine provocation (75 mg). Results: One third of patients (34%) had a positive history of histamine intolerance. There was no statistical difference between the mean UAS7 scores of patients with positive and negative histories (22.4 ± 1.0 vs. 22.7 ± 0.8). When kept on diet, 46% of patients responded with reduced CSU activity (UAS7 reduction of ≥7). Following double‐blind, placebo‐controlled oral histamine provocation, 17% of patients gave a positive weal response. There appeared to be little relationship between patient history, response to diet and the weal response to oral histamine provocation. First, the history‐positive and ‐negative groups contained similar proportions of diet and histamine provocation weal‐positive patients. Second, the diet‐positive and ‐negative groups contained similar proportions of history‐positive and histamine provocation weal‐positive patients. Third, the histamine provocation weal‐positive and ‐negative groups had similar rates of history‐ and diet‐positive patients. Finally, only 2 of the 157 patients were positive in all three domains. Conclusions: CSU due to histamine intolerance appears to be rare and cannot be diagnosed based on the history. The study confirms that avoidance diets low in pseudoallergens can improve urticaria symptoms, this is probably not due to the absence of dietary histamine.